Analisis Prosedur Pemberian Kredit Pada Koperasi Unit Desa (KUD) Tunas Sari Desa Bonea Kecamatan Lasalepa Kabupaten Muna - Andriani, Lila; Turi, La Ode; Halim, Muliha (Jurnal Online Program Studi Pendidikan Ekonomi, 2020)
This study aims to determine the implementation of credit granting procedures in the Village Unit Cooperatives Tunas Sari, Bonea village, Lasalepa District, Muna Regency. With data collection techniques through interviuw observation and documentation. Data obtained at the Village Unit Cooperatives Tunas Sari. Data analysis using descriptive qualitative. The results show that the procedure for granting credit in the Village Unit Cooperative Tunas Sari has fulfilled several procedures that include credit application procedures, credit analysis, credit decisions and credit disbursement. At the credit analysis stage using the 5C approach (Character, Capacity, Capital, Collateral dan Condition) those who did not meet the criteria averaged 0,74% peryear during 2013-2015.